2019
DOI: 10.1111/acel.13022
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐21‐5p/dual‐specificity phosphatase 8 signalling mediates the anti‐inflammatory effect of haem oxygenase‐1 in aged intracerebral haemorrhage rats

Abstract: Intracerebral haemorrhage (ICH) is a severe neurological disorder caused by bleeding within the brain tissue. Inflammation has been implicated in ICH pathogenesis and is a potential therapeutic target for ICH. Haemin, an activator of haem oxygenase-1 (HO-1), rapidly increases HO-1 protein expression and activity and has been shown to distinctly affect anti-inflammatory functions after central nervous system (CNS) injury. However, less is known about the mechanisms that underlie the antiinflammatory effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Moreover, very recently, it was reported that expression of serum miR-21 levels was notably elevated in atherosclerotic subjects and stroke patients relative to healthy individuals. Likewise, they also found that miR-21 strongly regulated the anti-inflammatory effect of haem oxygenase-1 (HO-1) in aged intracerebral hemorrhagic rats [24]. Besides, plasma microRNA-21 was also significantly correlated with platelet extracellular vesicles (EVs) in stable coronary artery disease patients [25].…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, very recently, it was reported that expression of serum miR-21 levels was notably elevated in atherosclerotic subjects and stroke patients relative to healthy individuals. Likewise, they also found that miR-21 strongly regulated the anti-inflammatory effect of haem oxygenase-1 (HO-1) in aged intracerebral hemorrhagic rats [24]. Besides, plasma microRNA-21 was also significantly correlated with platelet extracellular vesicles (EVs) in stable coronary artery disease patients [25].…”
Section: Discussionmentioning
confidence: 92%
“…Rapidly accumulating evidences have indicated that miRNAs are crucial regulators in ICH. 13,14 Exosomal miRNAs expression varies widely in different cell types and pathological states, and miRmodified Exos may alter its function. MiR-146a-5p is highly conserved among humans, mice, and rats.…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebral hemorrhage (ICH) occurs when a weakened vessel ruptures and bleeds into the surrounding brain [29,30]. Various forms of cell death have been identified after ICH, including apoptosis, necrosis, and autophagy in humans and experimental animals, and autophagic cell death in animal models [31][32][33]. Although inhibiting apoptosis, necrosis, and autophagy can improve outcomes in animals subjected to experimental ICH, no successful clinical trials using cell-death inhibitor monotherapy have been reported [34][35][36].…”
Section: Discussionmentioning
confidence: 99%